Intelligent Transportation Systems Efficiency - Marma, A.; Eidukas, D.; Žilys, M.; Valinevičius, A. (Elektronika ir Elektrotechnika, 2005)
Nowadays the quantity of vehicles in the Lithuanian cities is growing very fast. Loading on street intersections, traffic jams, wasting fuel and air pollution is increasing also. One of the ways to solve these problems is creating Intelligent Transportation Systems (ITS) and efficiency increasement of these systems. Quality parameters for ITS systems are: efficiency of data collecting system, volume and effectiveness of control system, adaptive and efficiency of algorithms. To project optimal and effective ITS systems structure, subsystems, installation and control places it is very important to evaluate efficiency for these systems. In this article we can find one of the possible ways for rating transport streams data collecting systems. After experiment (expert interrogatory method) results showed that video surveillance and digital analyzing of video signal is most efficient traffic flows data collecting technology used to control traffic flows and road intersections. Also in the article we can find efficiency evaluating methods for: video cameras, dislocation video cameras for road section and for data collection system. Ill. 6, bibl. 7 (in Lithuanian; summaries in Lithuanian, English and Russian).